Art Therapy dalam Konseling Islam untuk Mengurangi Kecemasan Siswa - Ahmad Maulana Ishak; Mukhlis Aliyudin; Reza Jaelani (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This research aims to formulate, implement, and evaluate the effectiveness of the integrated Art Therapy service model within the framework of Islamic Counseling to reduce students' academic anxiety at SMA Plus Al-Aqsha. The phenomenon of academic anxiety is identified not only as a clinical disorder, but as a form of spiritual shak (al-qalaq al-ruhi) which is rooted in the deficit of tawakal and the loss of inner peace (sakinah). Using a qualitative approach of a descriptive case study type, this study involves students who have high levels of anxiety and resistance to conventional verbal communication. Data was collected through participant observation, artwork documentation, and post-creation reflection in-depth interviews, which were then analyzed using the Miles, Huberman, and Saldaña interactive model. The research results show that operational procedures that include the stage of initiation (purification of intention), externalization (expressive painting), and transformation (internalization of the values of patience, gratitude, and husnuzan) are effective in reducing anxiety scores significantly. Painting media serves as a non-verbal cathartic instrument that is able to break down the psychological resistance of adolescents, while the integration of tawhid values provides a more permanent transcendental resolution than a secular approach. The synergy between emotional regulation through artistic expression and faith strengthening is proven to be able to transform the narrative of anxiety into stable spiritual calmness. This study concludes that the Art Therapy service based on Islamic Counseling is an innovative and contextual solution for counseling guidance practitioners in improving the mental health and quality of life of students in the Islamic education environment.